The legislative function of the senate and its relationship with the house of representative / Nor Akhmal Hasmin, Nurul Khairiah Dahalaan and Nurulyani Norzari - Hasmin, Nor Akhmal; Dahalaan, Nurul Khairiah; Norzari, Nurulyani (2008)
Dewan Negara is one of the legislative bodies which are responsible for law making process in our Parliament. It is a body for a matured deliberation and to avoid tyranny of a single house. However the Dewan Negara had deviate from its original roles. This is happen because of the occurrence of problem relating to rubber stamp legislature. Due to this, we had come out with this research that focusing on the factors which contribute to the problem of rubber stamp legislature. Besides that, we are also providing the recommendation on how to overcome this problem. By having this research, we hope that there is a change in the Dewan Negara to enhance its effectiveness. Therefore the law will truly represent the interest of the public.